Bildmakeri i feministisk regi - Andersen , Elin (Tidskrift för genusvetenskap, 1997)
There can be no doubt that many post avante-garde and experimental performances have been inspired by the phenomenon performance-art. How can one explain why this hybride art form oi development of traditional art has held such an attraction for experimental dramatical artists? Performanc- art cannot be placed within a certain genre or even form. It rather constitutes a free zone from which artists from different art forms can pick and choose from various media - a happening which is independent, whose roots rather can be traced to dance than other art forms. This article focuses upon the exchange between visual art and theatre within performance-art, specially the meeting between female artists. How far can we take analogies between the aestetics of visual art and the effects of visualisation on the stage? To illucidate these questions this article takes a closer look a one performance by the international L.O.T. Theatre from Braunschweig, Germany, RISSE BILDNISSE ZU FRIDA KAHLO, which crosses the borders of text, object, dance and music.